Pendampingan Asesmen Terhadap Guru Dalam Pemenuhan Standar Kesehatan Anak - Erna Budiarti; Yeni Heryani; Entri Mardiyanti; Eliyanah; Resti Widiyanti (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Training on Assessment of PAUD Teachers in Fulfilling Child Health Standards is a community service program designed with the main aim of increasing the knowledge and skills of Early Childhood Education (PAUD) teachers in assessing children's health. This training also aims to strengthen the capacity of PAUD teachers. in proactively identifying and dealing with various children's health problems, which in turn is expected to produce a healthier learning environment and contribute positively to the growth and development of early childhood in the Pademangan District area, North Jakarta. Through structured training methods, this program focuses on identifying the specific needs of PAUD teachers, preparing relevant training materials, as well as implementing training sessions involving opening and orientation, theory sessions, practical sessions, and evaluation and feedback. It is hoped that through this assessment training, PAUD teachers will be able to more effectively meet child health standards, improve the quality of learning, and make a positive contribution to early childhood development in Pademangan District, North Jakarta.